2004
DOI: 10.1007/s10047-003-0241-9
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of low-priming-volume cardiopulmonary bypass circuits and dilutional ultrafiltration in neonatal open-heart surgery

Abstract: In neonate open-heart surgery, cardiopulmonary bypass (CPB) with extreme hemodilution induces an increased capillary permeability and accumulation of extravascular fluid, resulting in organ dysfunction. We evaluated the effects of a reduced priming volume for CPB and dilutional ultrafiltration (DUF) during neonatal open-heart surgery. Nineteen consecutive neonates with complete transposition of the great arteries who underwent an arterial switch operation were retrospectively assigned into two groups: the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…During CPB, we frequently applied ultrafiltration to concentrate the circuit fluid. We believe that vigorous ultrafiltration is essential for the reduction of transfusion during CPB .…”
Section: Discussionmentioning
confidence: 99%
“…During CPB, we frequently applied ultrafiltration to concentrate the circuit fluid. We believe that vigorous ultrafiltration is essential for the reduction of transfusion during CPB .…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that low-prime volumes of CPB for neonatal cardiac surgery improve water balance during surgery and preserve postoperative organ function [15]. Meanwhile, recent papers indicate that higher haematocrit levels during CPB were associated with reduction in adverse perioperative and postoperative outcomes (haematocrit levels of 30% compared with 20%) [16].…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that low-priming CPB circuits in neonatal cardiac surgery improve water balance during surgery and preserve postoperative organ function [19]. The small priming volume allowed us to adjust hemodilution to a hematocrit of approximately 25% during CPB without additional blood transfusion.…”
Section: Discussionmentioning
confidence: 99%